Unlocking the Power of Capsaicin: A Comprehensive Review of Its Mechanisms and Applications - Sukmanadi, Mohammad; Khairullah, Aswin Rafif; Sudjarwo, Sri Agus; Effendi, Mustofa Helmi; Srianto, Pudji; Madyawati, Sri Pantja; Aulanniam, Aulanniam; Lamid, Mirni; Plumeriastuti, Hani; Mustofa, Imam; Akintunde, Adeyinka Oye; Wardhani, Bantari Wisynu Kusuma; et al. (Trends in Sciences, 2025)
Capsaicin is the main bioactive compound in chili peppers (Capsicum sp.) that has attracted widespread attention in pharmacology and health. This substance functions by stimulating the Transient Receptor Potential Vanilloid 1 (TRPV1) receptor, which is involved in the sense of pain, the control of body temperature, and inflammatory reactions. This study reviews the mechanism of action of capsaicin and its applications in various fields of health and clinical therapy. Capsaicin has diverse pharmacological effects, including as an analgesic, antioxidant, cardioprotective, anti-cancer, and metabolic regulator agent in the management of obesity. In addition, this compound shows potential in neurodegenerative therapy, such as Alzheimer’s and Parkinson’s diseases, by reducing oxidative stress and neuroinflammation. Capsaicin also has gastroprotective, dermatoprotective, antimicrobial, and anti-inflammatory effects, making it a potential ingredient in various medical applications. However, side effects such as gastrointestinal irritation, burning sensation, and possible long-term toxicity need to be considered in its use. Therefore, further research is needed to develop safer and more effective formulations. In addition to its medical applications, capsaicin is also used in the food and biotechnology industries. With a deeper understanding of its mechanisms of action such as affecting the nervous system, body fat profiles, and controlling hunger and other mechanisms described in this paper, capsaicin has the potential to be an important component in the development of molecular-based therapies. Further studies are needed to optimize its therapeutic benefits and explore its safety in broader clinical applications. HIGHLIGHTS Capsaicin exerts its biological effects primarily through activation of the TRPV1 receptor, inducing calcium influx and neuropeptide release that mediate pain perception, thermoregulation, and inflammatory responses. Capsaicin demonstrates a broad spectrum of pharmacological properties, including antioxidant, anti-obesity, cardioprotective, anticancer, and antimicrobial activities via multiple cellular pathways. Capsaicin shows therapeutic potential in the management of neurodegenerative and metabolic disorders such as Alzheimer’s disease, Parkinson’s disease, and obesity by modulating oxidative stress and metabolic signaling mechanisms. Capsaicin’s clinical applications are limited by adverse effects, such as local irritation and gastrointestinal discomfort, thereby necessitating the development of safer and better-tolerated analogs. The discovery of endogenous and synthetic TRPV1 ligands reinforces capsaicin’s therapeutic relevance beyond nociception, extending to cardiovascular, dermatological, and gastrointestinal health. GRAPHICAL ABSTRACT